Using TikTok as a Media to Enhancing Speaking Skills in English Foreign Language Classroom: A Lesson Learned from ESP Contexts - Waode, Waode Hamsia (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
The TikTok application is a social media platform that allows users to upload and edit videos using a variety of features to create content as desired. Its accessibility via mobile phones means that it can be used for online learning anywhere and anytime, effectively functioning as a mobile learning (m-learning) tool. This research focused on utilizing TikTok as a medium to enhance speaking skills in English as a foreign language (EFL) classrooms. This study employed a qualitative approach to explore the effectiveness of TikTok in improving students' English speaking skills. Data for the research were collected through observations and questionnaires. The study involved 20 students from the Marine Engineering program at Universitas Muhammadiyah Surabaya. Through careful analysis of the collected data, the research aimed to determine the impact of TikTok on students' speaking abilities. The results indicated that using TikTok as a medium significantly improved speaking skills in the EFL classroom. Students showed enhanced proficiency in their spoken English, attributed to the engaging and interactive nature of the platform. The study concluded that TikTok is an effective tool for improving students' speaking skills in English as a foreign language. Therefore, incorporating TikTok into EFL instruction can successfully enhance students' speaking abilities, making it a valuable resource for language educators.